International Handbook of Lifelong Learning
LVIII, 820 p.
Keywords: Recent changes in the world effected by the transformations of information technology, globalisation, and the move towards a knowledge economy over the last thirty years have been as radical and fundamental as the changes resulting from the invention of the wheel and the printing press. We are now living in a new age in which the demands are so complex, so multifarious and so rapidly changing that the only way in which we shall be able to survive them is by committing to a process of individual, communal, and global learning throughout the lifespan of all of us. A number of international bodies and agencies have taken cognisance of these transformations and the demands they impose upon societies and communities of the twenty-first century and have developed and articulated policies intended to enable all citizens of the world in the twenty-first century to face these challenges. It is now a declared policy of many governments and international agencies that the only vehicle for such preparation is `education, education, education', and that preparing for the knowledge economy and the learning society of the future has to be a lifelong undertaking, an investment in the future that is not restricted merely to the domain of economic advancement but also to those of social inclusion and personal growth. Realising this, policy-makers across the international arena are grappling with the need to move from systems that emphasise education and training to the radically more unworked construct of lifelong learning. In this volume the editors and authors analyse, criticise, and rework the ideas, principles, and theories underpinning policies and programs of lifelong learning, re-interpreting them in the light of examples of `best practice' found in a range of educating institutions around the world. We believe that students of educational change and community development will find it useful and helpful to have available in this volumesome of the most up-to-date thinking on the chief concepts, theories, and values of increasing policy interest in lifelong learning, together with a review of some significant examples of the different forms, focuses, and nexuses of thought and practice on this topic. All this enables us to offer some policy recommendations and practical suggestions as to ways forward in the endeavour to make lifelong learning a reality for all.